Hydrogen storage properties and mechanisms of as-cast, homogenized and ECAP processed Mg98.5Y1Zn0.5 alloys containing LPSO phase. (15th February 2021) - Zhang, J.; Yao, Y.; He, L.; Zhou, X.J.; Yu, L.P.; Lu, X.Z.; Peng, P.
Abstract: In this work, three different states (as-cast, homogenized and ECAP processed) of Mg98.5 Y1 Zn0.5 alloys with high theoretical hydrogen storage capacity (7.2 wt%) were prepared and comminuted into chips by filing. Then their hydrogen storage properties and underlying mechanisms were systematically investigated through experimental and first-principles calculations approaches. The results show that the activation properties of these alloys are enhanced in the order of homogenized, as-cast and ECAP processed states, which is closely associated with the size of filed chips. After activation, the as-cast and ECAP processed samples exhibit the superior hydrogen adsorption/desorption kinetics compared with the homogenized one. Interestingly, the as-cast sample presents the similar or even better kinetics relative to the ECAP processed one. This should be attributed to the more uniform dispersion of in - situ formed YH2 nanohydride in the as-cast alloy, which remarkably boosts the reversible hydrogen storage properties of Mg matrix by the synergistic pinning and catalytic effects. First-principles calculations reveal that the doping of Y not only reduces the activation energy of H2 dissociation on Mg surface, but also decreases the hydrogen removal energy of H atom from MgH2 bulk, which accounts well for the excellent hydrogen sorption kinetics of Mg98.5 Y1 Zn0.5 alloys. Highlights: Hydrogen storage properties of different states of Mg98.5 Y1 Zn0.5 alloys are studied. As-cast and ECAP samples exhibit superior kinetics relative to homogenized one. As-cast sample presents similar or better kinetics relative to ECAP processed one. In-situ formed YH2 nanohydride plays pinning and catalytic effects on Mg matrix. Hydrogen storage mechanisms of Mg98.5 Y1 Zn0.5 are revealed based on DFT calculations.